A inserção do setor privado na educação básica municipal e seus efeitos nas políticas públicas educacionais - Gabriel, Angelica Felske (2023)
This Professional Master degree dissertation is included in the research field called Higher and Basic Education Management and Policies, of the Pos Graduation Program in Public Policies and Educational Management (LP1) – PPPG, of the Federal University of Santa Maria (UFSM) and its theme lies on the implications of the public-private relations in the public policies of the basic education and on the implementation of the apostille system linked to the digital platform of teaching, from the year 2021 to 2023. It aims to understand how the relations between the public and the private sectors have impacted on the teaching-learning processes of a municipal school in the rural area of the city of São Pedro do Sul/RS, considering the implementation of the apostille system, which is linked to the digital platform “Learn Brazil System” (Sistema Aprende Brasil), during the pandemic period. As a methodology, it was used the qualitative method, in the perspective of a case study in a countryside school in the city of São Pedro do Sul/RS. The research instruments were organized in two stages: the study of the theoretical and documental reference (Lei Municipal n. 2531/2015, Ofício Municipal N. 103/2022/GP, Parecer N. 03/2021 do CME, Contrato de Inexigibilidade); and the narratives obtained from thematic (self) biographical interviews with four elementary school teachers who work with the initial and final grades and were voluntary.Later, the comprehensive-interpretative analysis was developed (SOUZA, 2004; 2014; BOLÍVAR, 2002). The following theoretical reference was used for this work: Chrispino (2016; 2005); Santos (2020); Adrião and Peroni (2009); Adrião et al (2016); Abrahão (2003); Peroni (2015); Saura, Gutiérrez and Vargas (2021); Freitas (2018); Freire (1996; 1987; 2001; 2007); Clandinin and Conelly (2011); Dourado and Bueno (2001); among others. The construction of the final product was the creation of an advising guide from the authors being studied as well as the narrative interviews with the four volunteer teachers who participated of the implementation of the “Learn Brazil System” and work at the school which is the locus of this study. The advising guide aims to cooperate with the teaching-learning process developed by the school of this study, based on the specificities of a school located in the countryside, of the rural area in the city of São Pedro do Sul, besides contributing to the permanent teaching formation of the participants and also of the teachers who will have access to the advising guide.